Features of angular distributions of 1 GeV electrons scattered by thin silicon monocrystal - Fomin, S.P.; Shcherbak, S.F.; Kasilov, V.I.; Lapin, N.I.; Shul'ga, N.F. (Вопросы атомной науки и техники, 2001)
The result of theoretical and experimental investigations of angular distribution structure of 1 GeV electrons scattered by silicon crystal of 10 mm thickness are presented. The electron beam was falling on the crystal under different angles (from zero to the critical channeling angle) in respect to the crystal axis <111>. The analysis of the experimental data was carried out with the help of computer simulation of electron beam passage through the crystal on the basis of binary collision model. It is shown, that the existence of several maxima in the angular distributions of scattered electrons is stipulated by contributions of different fractions of electron beam in crystal, namely: the channeled and the above-barrier. The combined technique (simulation-experiment) of investigation of elastic scattering makes it possible to obtain important quantitative information about relativistic electron beam dynamics in aligned crystals.